1990
DOI: 10.1139/o90-109
|View full text |Cite
|
Sign up to set email alerts
|

Esterase activity of high-Km aldehyde dehydrogenase from rat liver mitochondria

Abstract: Aldehyde dehydrogenase possessing an esterolytic activity has been purified to homogeneity from rat liver mitochondria. Steady-state kinetic studies suggest that the esterolytic reaction follows an ordered uni-bi mechanism. The formation of an acyl enzyme intermediate via nucleophilic catalysis during the esterase reaction is established kinetically using a series of substrates with varying acyl carbon chains and substituted phenyl octanoates with varying electronic effects. The enzyme was reconstituted into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…These results are in accordance with the observation that the mitochondrial ALDH provides an important bioactivation pathway for GTN [19,20,24,25] and is redox-sensitive [36,37] (see scheme in Figure 4). These facts provide a new link between oxidative stress and impaired GTN bioactivation and accordingly development of tolerance: Mitochondrial ROS oxidatively inactivate the ALDH-2.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in accordance with the observation that the mitochondrial ALDH provides an important bioactivation pathway for GTN [19,20,24,25] and is redox-sensitive [36,37] (see scheme in Figure 4). These facts provide a new link between oxidative stress and impaired GTN bioactivation and accordingly development of tolerance: Mitochondrial ROS oxidatively inactivate the ALDH-2.…”
Section: Discussionsupporting
confidence: 91%
“…This is not contradictory, because ALDH-2 contains three cysteine residues in the catalytic center (Fig. 7), rendering the dehydrogenase activity highly sensitive toward oxidative inactivation (Senior and Tsai, 1990;Tsai and Senior, 1991). In addition to Fig.…”
Section: Discussionmentioning
confidence: 93%
“…5A (right axis) defines the level of total esterase activity in control mitochondria, whereas line 2 defines the oxidation-resistant esterase activity. The esterase activity of ALDH-2 involves redox-sensitive sulfhydryl groups and should be inhibited by oxidants (Senior and Tsai, 1990;Tsai and Senior, 1991). Therefore, this activity is represented by the difference between lines 1 and 2.…”
Section: Downloaded Frommentioning
confidence: 99%
“…5). Both activities seem to involve cysteine thiol groups (15,32) and are inhibited by oxidants and thiol-targeted compounds such as Ellman's reagent (8). In 2002, an additional function was attributed to this enzyme when Chen et al (5) identified ALDH-2 as a GTN-bioactivating enzyme.…”
Section: Discussionmentioning
confidence: 99%